Analisis pengelolaan Alokasi Dana Desa (ADD) berdasarkan Peraturan Bupati Nomor 19 Tahun 2023 di Kampung Yakonde, Distrik Waibu, Kabupaten Jayapura - Wally, Ghina Maurista; Sabijono, Harijanto; Walandow, Stenly Kho (Yayasan Widyantara Nawasena Raharja, 2025)
Management of village fund allocation is the obligation of parties to provide accountability, present, report, and disclose all activities and actions regarding fund allocated by the regency government for villages. This fund originates from the share of central and regional financial balance funds received by the regency or city to support all sectors in society. This research aims to analyze the management of village fund allocation (ADD) in Yakonde village, Waibu District, Jayapura Regency. The analytical method used is descriptive, and each data collected is analyzed to draw conclusions. The research is descriptive and qualitative. The results are clear: village fund allocation (ADD) management in Yakonde village, Waibu District, Jayapura Regency is being implemented in accordance with Regent Regulation No. 19 of 2023 concerning village financial management.